The landscape of Galicia from the perspective of Otero Pedrayo: the interdisciplinarity and the influence of romanticism (Nudos. Revista Transdisciplinar de Sociología, Teoría y Didáctica de la Literatura, 2018)
Ramón Otero Pedrayo has been one of the most representative Galician humanists of the 20th century. Professor of Geography at the University, he was a researcher who took care of studying, among other things, the landscape of his native region, Galicia.The present work has as objective to see the imprint of the landscape in the academic field, and especially to analyze its landscape studies from the geographic point of view, but at the same time taking into account the need to interrelate, not only this science, but other disciplines that grant a vision of the territory as a whole. A landscape with scientific basis, which, in some cases, will include the romantic vision of some of the most representative Galician writers of Romanticism and  rexurdimento galego , which will allow it to become an emblem of identity of this territory.
Keywords: Otero Pedrayo; landscape; Galicia; geography; interdisciplinary